Formulation and Characterization of Cayenne Pepper (Capsicum Frutesens L.) Leaf Extract Spray as Anti Acne - Multiani S. Latif; Moh. Aprianto Paneo; Pratiwi Abdullah (Jurnal Ilmiah dr. Aloei Saboe, 2023)
This study aims to formulate cayenne pepper leaf extract (Capsicum frutescens L.) as an anti-acne to spray preparation and to determine the effect of the formulation of cayenne pepper leaf extract (Capsicum frutescens L.) as an anti-acne on the characterization of spray preparations. The method used in this study is experimental (laboratory experiments) based on differences in the concentration of carbopol bases in each formula. The carbopol concentrations were: Formula I (0.5%), Formula II (1%), Formula III (2%). The results showed that in the characterization test of the spray preparation of cayenne pepper leaf extract (Capsicum frutescens L.) physically cannot be made in spray dosage form because the results obtained still leave color and are not clear when viewed from the terms of the preparation, but the physical stability of the preparation for formula I, formula II and formula III from the results of the parameters of the preparation characterization test, statistical data analysis with one sample T.Test where the significance value of P 0.05 indicates that there is an effect on the characterization of the preparation.